Cutting our losses: The effects of a loss-aversion strategy on student learning gains. Issue 1 (2nd January 2023) - Olitsky, Neal H.; Cosgrove, Sarah B.
Abstract: In this randomized controlled trial with controls for student characteristics, the authors used a loss-aversion strategy to test whether students achieve greater learning gains from combining research-based instructional strategies with loss aversion. Students in the control group began the class with no grades and built their course average by completing assignments and exams. The treatment group began with a score of 100 percent on each assignment and viewed the deductions on scores from errors and missed work. The results indicated that students in the treatment group experienced gains in learning that were, on average, 5 to 13 percentage points larger than those of the control group. These learning gains were concentrated among students with low SAT math scores.